Arctic Blue Resort Kontiolahti – Co-responsibility handbook - Wilenius, Markku; Jones, ,Ana Maria (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2020)
This handbook introduces important criteria on co-responsibility standards in hospitality for a new ecological development, the Arctic Blue Resort Kontiolahti in North Karelia. The resort initiative stems from a rich Nordic tradition of honesty, respect and appreciation for nature. It builds on key assets characterizing the region, namely: access to high-quality of air, pure drinking water and pristine forest lands. The resort also rests on the hospitable and environmentally-conscious culture of Karelia and its friendly people considered one of the happiest in the world. The development is unique in that it combines the virtues and healing powers of nature, with efficiency and high standards for environmental hospitality development, products and services. The sustainability guidelines introduced in this handbook draw from a literature review on the state of global tourism and from case studies of well-stablished advanced sustainability practices in hospitality and ecotourism outside of Finland. Taking the lessons from these examples, the new Arctic Blue Resort Kontiolahti aims at a new level of ecological and restorative tourism. The resort has unique capacities for providing visitors with a mix of extremely pure bounties of nature coupled with a nature-based design in all the new infrastructure planned for the area. Furthermore, by using a human and nature-centric design, the resort aims to make a positive and lasting impact on the state of nature areas as well as on the local and regional communities. The Arctic Blue Resort Co-Responsibility Handbook has been prepared for the Kontiolahti Municipality in collaboration with the Finland Futures Research Centre, the Arctic Brands Group and Innvolve Oy in Helsinki. The information contained in this handbook is intended for the general public with the hope that this new development plants the seeds of a new culture of tourism and travel in North Karelia-Finland built on the highest ecological standards with collective responsibility and care for people and nature.